PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS ADOBE FLASH CS4 PADA POKOK BAHASAN IKATAN KIMIA SMA/MA - Rizki Adi Yona; Betty Holiwarni; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Purpose of this study was to develop learning media based on Adobe Flash CS4 chemistry to produce a decent learning media on the subject of chemical bonding that is developed based on the feasibility aspect of design, pedagogy, content, ease of use in Chemical Education Program. This media development research using ADDIE model of which has 5 stages of development, namely analysis, design, development, implementation and evaluation. Model development is modified by the only research to the development phase (development). Results of research-based instructional media development Adobe Flash CS4 on the subject of chemical bonds that have been validated by a validator to be feasible with an average percentage of 97.45% and 91.37%. This indicates that the learning generated media fit for use as a medium of learning.